KUALITAS PELAYANAN PEMBUATAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIGI - Fadhila, Fadhila (Katalogis, 2014)
This study aims to analyze birth certificate making service quality at the Departmen OfPopulation and Civil Registration Sigi Regency. The unit of analysis in this study was all employees off the Affice of Population and Civil Registration Sigi. Wich were around 30 people and the citizens as the users of the birth certificate 5 people has been assiegned as the informant for this study in which the head Office of population and civil registration Sigi as the key informant. The number of informant will be added as needed if the information obtained is not achieved. The data collection techniques used in this study are observation, interview and documentation. The results showed that the quality of birth certificate service at the Departement of Population and Civil Registration Sigi Regencyconsists of four indicators. Firstly, the length of birth certificatemaking process has been carried out in predetermined time. Second indicatoris the management of processing a birth certificate is also straightforward by condition all requirements are met. Third indicator is the high accuracy of the birth certificate wish minimum errors. Last;y, the cost of care for those who experience a delay is low. The support factor are the education level, years of service, and human resources. Whreas the constraint factors are infrastructure, dci[line, leadership and job location.